Compound cis-regulatory elements with both boundary and enhancer sequences in the human genome - Jjingo, Daudi; Wang, Jianrong; Conley, Andrew B.; Lunyak, Victoria V.; Jordan, I. King (Bioinformatics, 2013)
It has been suggested that presumably distinct classes of genomic regulatory elements may actually share common sets of features and mechanisms. However, there has been no genome-wide assessment of the prevalence of this phenomenon. Results: To evaluate this possibility, we performed a bioinformatic screen for the existence of compound regulatory elements in the human genome. We identified numerous such colocated boundary and enhancer elements from human CD4þ T cells.We report evidence that such compound regulatory elements possess unique chromatin features and facilitate cell type-specific functions related to inflammation and immune response in CD4þ T cells.
Keywords: Compound cis-regulatory elements; Enhancer sequences; Human genome